Profil Kemampuan Literasi Lingkungan Siswa Kelas VIII dalam Pembelajaran IPA - Ayu, Ika; Sari, Eka (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2023)
This research aims to determine the profile of environmental literacy abilities of class VIII students in learning science at SMP Negeri 5 Demak. This research is a qualitative descriptive study. The population in this study were all class VIII students with a sample size of 167 class VIII students at SMP Negeri 5 Demak. Sampling used the proportionate random sampling technique, and determining the number of samples used the Slovin formula with an error rate of 5%. Data collection methods use tests, observation, interviews and documentation. The test given uses an environmental literacy questionnaire based on MSELS (Middle School Environmental Literacy Survey). The research results show that in general the environmental literacy level of class VIII students at SMP Negeri 5 Demak is classified as good at 89% with an average score of 66.64. Good literacy test results are supported by school management regarding a good environmental literacy program, the biology learning process in applying environmental literacy concepts, the school's vision, mission and goals which support the implementation of a literacy-based school, and school infrastructure which is able to support literacy activities. student environment.